tìm x
a) x+1=89
b) x+68=-100
Tìm x
a) (x-1)^10 + (x-2)^10 =1
b) (x+3)^100 + (x+4)^100 = 1/3
Tìm x
a) (x-1)^10 + (x-2)^10 =1
b) (x+3)^100 + (x+4)^100 = 1/3
Tìm x
a) (x-1)^10 + (x-2)^10 =1
b) (x+3)^100 + (x+4)^100 = 1/3
Tìm x
a) (x-1)^10 + (x-2)^10 =1
b) (x+3)^100 + (x+4)^100 = 1/3
Tìm x
a) (x-1)^10 + (x+2)^10 =1
b) (x+3)^100 + (x+4)^100 = 1/3
Tìm x
a) 35.5²⁰²¹-4.5^x=3.5²⁰²¹
b) x+(x+1)+(x+2)+...+(x+100)=6565
b) x+(x+1)+(x+2)+...+(x+100)=6565
( x + x + x +...... + x) + ( 1 + 2 + 3 + ..... + 100) = 6565
Có tất cả số hạng là số tự nhiên là
\(\left(100-1\right):1+1=100\left(số\right)\)
Tổng các số tự nhiên là
\(\left(100+1\right).100:2=5050\)
Có tất cả số hạng là số x
100 + 1 = 101
101x - 5050 = 6565
101x = 6565 + 5050
101x = 11615
x = 11615 : 101
x =115
bài 1:tìm x biết
a,(125-x)+25=98
b,100:(x+20)=68:34
c,(3.x+12).5=25.4-10
d,210:(2.x-3)-20=10
a) (125 - x) + 25 = 98
125 - x = 98 - 25
125 - x = 73
x = 125 - 73
x = 52
b) 100 : (x + 20) = 68 : 34
100 : (x + 20) = 2
x + 20 = 100 : 2
x + 20 = 50
x = 50 - 20
x = 30
c) (3x + 12) . 5 = 25 . 4 - 10
(3x + 12) . 5 = 100 - 10
(3x + 12) . 5 = 90
3x + 12 = 90 : 5
3x + 12 = 18
3x = 18 - 12
3x = 6
x = 6 : 2
x = 3
d) 210 : (2x - 3) - 20 = 10
210 : (2x - 3) = 10 + 20
210 : (2x - 3) = 30
2x - 3 = 210 : 30
2x - 3 = 70
2x = 70 + 3
2x = 73
x = 73/2
a, ( 125 - x ) + 25 = 98
⇒ 125 - x = 73
⇒ x = 52.
Vậy..
b, 100 : ( x + 20 ) = 68 : 34
⇒ 100 : ( x + 20 ) = 2
⇒ x + 20 = 50
⇒ x = 30
Vậy...
c, ( 3 . x + 12 ) . 5 = 25 . 4 - 10
⇒ ( 3 . x + 12 ) . 5 = 90
⇒ 3 .x + 12 = 18
⇒ 3x = 6
⇒ x = 2.
Vậy...
d, 210 : ( 2 .x - 3 ) - 20 = 10
⇒ ( 2 .x - 3 ) - 20 = 21
⇒ 2x - 3 = 41
⇒ 2x = 44
⇒ x = 22.
Vậy..
Cho mk chỉnh lại câu cuối:
d, 210 : ( 2 .x - 3 ) - 20 = 10
⇒ 210 : ( 2 .x - 3 ) = 30
⇒ 2 . x - 3 = 7
⇒ 2x = 10
⇒ x = 5.
Vậy..
Tìm X:
XX - 2X x 2 + 68 = 100
XX-2X x 2 +68=100
\(x^2-4x+68=100\)
\(X^2-4X-32=0\)
(X-8) x(X+4)=0
X=8 hoặc x=-4
Tìm n,biết:
n x 68 - 24 x n - n x 34 = 100
\(n\times68-24\times n-n\times34=100\)
\(n\times\left(68-24-34\right)=100\)
\(n\times10=100\)
\(n=100:10\)
\(n=10\)
Vậy \(n=10\)
n x 68 - 24 x n - n x 34 = 100
n x (68-24-34) = 100
n x 10 = 100
n = 100:10
n = 10
Vậy n=10